Strategi Komunikasi Guru Dalam Mengatasi Bullying Di Sekolah (Studi Di Lingkungan Sekolah SMP PGRI 7 Jakarta) - Noviana Putri Harahap, Sitka Bella; Sidharta, Veranus (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Bullying at school has become a serious problem that affects students' psychological and academic development. This phenomenon can cause various negative impacts, including decreased academic performance, increased stress levels, anxiety, and depression. This research aims to explore various communication strategies used by teachers in dealing with bullying at school. The method used in this research is qualitative research using a constructivist paradigm to understand and construct teacher communication strategies in overcoming bullying in the PGRI 7 Jakarta school environment. The research results show that teacher communication strategies at SMP PGRI 7 Jakarta have a central role in preventing bullying by implementing a holistic approach. First, build a positive school culture. Second, increase supervision through routine patrols. Third, openness in communication. Fourth, build personal relationships with students. Fifth, build communication with parents through regular meetings. By implementing this strategy comprehensively, teachers at SMP 7 PGRI Jakarta succeeded in creating a harmonious learning environment, free from bullying, and providing maximum support for students' overall development.